2018
DOI: 10.4049/jimmunol.1800468
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient IL-10 Production as a Mechanism Underlying the Pathogenesis of Systemic Juvenile Idiopathic Arthritis

Abstract: Systemic juvenile idiopathic arthritis (sJIA) is a childhood-onset immune disorder of unknown cause. One of the concepts is that the disease results from an inappropriate control of immune responses to an initially harmless trigger. In the current study, we investigated whether sJIA may be caused by defects in IL-10, a key cytokine in controlling inflammation. We used a translational approach, with an sJIA-like mouse model and sJIA patient samples. The sJIA mouse model relies on injection of CFA in IFN-g-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
0
17
0
3
Order By: Relevance
“…In fact, 2 independent studies in systemic JIA cohorts showed increased prevalence of IL10 promoter haplotypes that encode for low IL-10 expression (83,84). Recently, cell-specific IL-10 defects were observed in patients with systemic JIA and in a murine disease model, resulting in insufficient IL-10 production to counterbalance proinflammatory cytokines (85).…”
Section: Fromautoinflammationtoautoimmunitymentioning
confidence: 99%
“…In fact, 2 independent studies in systemic JIA cohorts showed increased prevalence of IL10 promoter haplotypes that encode for low IL-10 expression (83,84). Recently, cell-specific IL-10 defects were observed in patients with systemic JIA and in a murine disease model, resulting in insufficient IL-10 production to counterbalance proinflammatory cytokines (85).…”
Section: Fromautoinflammationtoautoimmunitymentioning
confidence: 99%
“…Arthritis was not observed in the experiments, most likely because the mice were sacrificed before onset of arthritis [joint inflammation is a late feature seen in CFA-challenged IFN-g KO mice (21)]. A parameter that may predict the potential development of arthritis is the formation of TRAP + -multinucleated osteoclasts ex vivo as described by Imbrechts et al (24). Splenocytes were stimulated with osteoclastdifferentiating factor RANKL and M-CSF, and after 7 d the osteoclasts were stained for TRAP.…”
Section: Resultsmentioning
confidence: 99%
“…For differentiation to osteoclasts, the cells were incubated with receptor activator of NF-kB ligand (RANKL; 100 ng/ml; R&D Systems) and M-CSF (20 ng/ml; R&D Systems). After 3 d, the cells were restimulated with fresh medium and stimuli for 3-4 d, followed by staining of the cells for tartrate-resistant acid phosphatase (TRAP) as described (23,24).…”
Section: Histologic and Cytospin Analyses Cell Isolation And Enrichmentioning
confidence: 99%
“…In a study published by Imbrechts et al, experimental evidence was provided on a mouse model that there would be a relationship between IL-10 insufficient production and its consequence in the innate cellular immune response from sJIA pathogenesis [58].…”
Section: Molecular and Cellular Mechanisms Of Systemic Arthritismentioning
confidence: 99%